Tradycja ustna versus pisana. Ustalanie obrzędowości i (re)konstruowanie tradycji w klasztorach żeńskich na przykładzie działalności s. Domiceli Barbary Fox, klaryski starosądeckiej - Borkowski, Igor (Uniwersytet Wrocławski. Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych, 2015)
In the context of chronicle records, personal documents and monasterial practice, the paper reconstructs the manner of transferring the content of oral tradition connected with historical and ceremonial customs of the monasterial community into written form. The documented process of writing down oral accounts of the foundation of the monastery, its architecture, the purpose of its different rooms as well as their function and its evolution throughout centuries, can be observed in the self-reflection of a Poor Clare nun from Stary Sacz, who is very passionate about history. A similar process applies to the realm of tradition, customs and habits formed in the community, which have been successfully captured in the process of transforming from the oral to the written tradition. Verifying the oral tradition, assessing oral and written accounts, as well as writing down and verifying the content of written records as analysed in this paper relate to archival resources that have not yet been published. They remain at the disposal of the Poor Clares Monastery in Stary Sacz and date back to the mid-19th century.
Keywords: oralność; obrzędy; tradycja; zakon klarysek; Stary Sącz